2017
DOI: 10.1002/ana.25015
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐137 and microRNA‐195* inhibit vasculogenesis in brain arteriovenous malformations

Abstract: Our results indicate that miR-137 and miR-195* act as vasculogenic suppressors in AVMs by altering phenotypic properties of AVMSMCs, and that the absence of miR-137 and miR-195* expression leads to abnormal vasculogenesis. Ann Neurol 2017;82:371-384.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…41,42 Previous studies demonstrated that NBP could promote angiogenesis. 38,39 The incidence of ischemic stroke and the infarct volume were decreased with NBP pretreatment in stroke-prone renovascular hypertensive rats. 22,43 In addition, NBP treatment within 24 hours after ischemic stroke rescued brain tissue by enhancing angiogenesis or opening collateral vessels, which was associated with the upregulation of VEGF and HIF-1α expression, in the stroke-prone renovascular hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Previous studies demonstrated that NBP could promote angiogenesis. 38,39 The incidence of ischemic stroke and the infarct volume were decreased with NBP pretreatment in stroke-prone renovascular hypertensive rats. 22,43 In addition, NBP treatment within 24 hours after ischemic stroke rescued brain tissue by enhancing angiogenesis or opening collateral vessels, which was associated with the upregulation of VEGF and HIF-1α expression, in the stroke-prone renovascular hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…A tube formation assay was carried out as previously described. 39 Matrigel (BD Biosciences, Franklin Lakes, NJ) was added into a 96well plate and incubated at 37°C for 30 minutes to allow solidification. Then, 2 × 10 4 HUVECs suspended in 30% CM of the four astrocyte groups and 70% endothelial cell medium were seeded into the coated plate in triplicate.…”
Section: Cell Tube Formation Assaymentioning
confidence: 99%
“…Intracranial aneurysm tissues were obtained from the brain tissues of 3 IA patients during microsurgery. The modified isolation protocol was based on a previously described study ( Bygglin et al, 2011 ; Huang et al, 2017 ). After clipping, the samples were immediately collected into DMEM supplemented with 5% penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The present study predicted the interaction of circRNAs and miRNAs. Among them, miR-137 targeted by circRNA_100933, has been reported to act as tumor suppressor in various tumors [ 41 , 42 ]. Previous study demonstrated that miR-216a-3p, one of the target miRNAs of circRNA_104310, inhibited gastric and colorectal cancer cell proliferation and migration [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%